Pengaruh Pemanfaatan Teknologi Informasi, Fungsi Badan Pengawas Dan Tingkat Pemahaman Akuntansi Terhadap Kualitas Laporan Keuangan Pada Lembaga Perkreditan Desa (LPD) Di Kecamatan Kediri - I Komang Gita Wedananta; Ni Komang Sumadi; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2025)
LPD as a financial institution has the obligation to make financial reports as an accountability for ongoing economic activities and as a basis for making decisions. This research aims to examine the influence of the use of information technology, the function of supervisory bodies, and the level of understanding of accounting on the quality of financial reports. This research was conducted at the Village Credit Institution in Kediri District. The sample in this research was 84 samples using a purposive sampling technique, namely a technique for determining samples with certain considerations or criteria. This research method uses quantitative research methods with primary data obtained from questionnaires which are measured using the Likert scale research method. The data analysis techniques used are validity test, reliability test, descriptive statistical analysis, classical assumption test, multiple linear regression analysis, coefficient of determination test (R2), F test and t test. The research results show that the use of information technology has a positive and significant effect on the quality of financial reports. The function of the supervisory body has a positive and significant effect on the quality of financial reports. The level of accounting understanding has a positive and significant effect on the quality of financial reports.